Pengaruh Non-Probability Sampling Batubara terhadap Parameter Dry Ash Antara Certificate of Analysis Loading dan Unloading - Denny Murdany Muchsin (Sekolah Tinggi Teknik - PLN, 2020)
Umpire test (referee test) may be conducted by the coal supplier based on the potential loss due to the difference Certificate of Analysis (COA) in both ports (loading and unloading). The purpose of the research was to determine a comparison of COA from non-probability sampling compiled with standard. The research method used quantitative methods by collecting COA data on both ports. These data on the receipt of coal was obtained from a coal-fired steam power plant (PLTU). A Sampling at both ports was conducted by the non-probability sampling method. The assumption was determined that the sample preparation and analysis process had complied with the American Standard Testing and Material (ASTM) standards. The ratio of ash (dry basis) in both COA to its average was processed statistically by taking confidence intervals with a confidence level of 95%. This research showed that the ratio was in the range of 10.213% up to 16.793%, exceeding precision 10% as required by ASTM D2234-16. Therefore, the comparison of COA data from non-probability sampling, could not be used as a reference for the doubt of the work of independent surveyors e.g. COA unloading, then it is technically that umpire test could not be conducted by such comparison.